Methods of Media Treatment of Political Issues in Investigative Television Programs- Program (What is hidden from Al Jazeera) as a model - Saba, Bushra Dwood (Journal of Humanities & Social Sciences, 2019)
This research aims to know the methods of media treatment of political issues in investigative television programs, based on the survey method, and the method of analyzing the content of a sample of the episodes of the investigative television program (what is hidden) on the screen of Al- Jazeera. The results revealed that the category of specialized experts ranked first Among the sources that rely on these programs (41.9%), the category of documents and official books came in second place (18%), and the category of eyewitness came from people who give information about the events that witnessed the third place (14.5%). The results of the analysis also showed that the highest percentage of meanings and ideas included in the program's episodes (what is hidden is greater), meanings that involve the values ​​of violence (47.4%), while the meanings of international terrorism (25%), and the meanings of the conflict ranked Third (11.5%). The results of the research showed a clear bias to one party at the expense of the other during the presentation of political issues, and in the light of the findings of the research the researcher has made a number of recommendations, the most important of which are: Increasing the effectiveness of investigative television programs, by increasing the time allocated to them. Supporting the staff working in these programs financially and morally, as well as allowing them to participate in training courses organized by Arab and international networks specialized in investigative journalism. Always ensure that the content of these programs is far from bias and imbalance, whether in the presentation of information or in the selection of personalities and sources, and that they have the following features: Presentation of divergent views (opinion and other opinion) within the framework of objectivity and address issues from different angles.
Keywords: investigative TV programmes; Ma Hidden Greater; Al Jazeera channel